(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The local administration must direct most of its attention to planning and implementing projects that serve the community now and in the future and have a material economic return that contributes to supporting the governorate’s treasury, and contributes to creating job opportunities that reduce the unemployment rate and absorb excess labor, without focusing only on implementing typical service projects that ministries can implement. Through its central departments in the governorate through the investment plan of each ministry. It is necessary to diversify development plans in terms of their inclusion of advanced sectors of projects, such as electric power projects, water supply, and sewage treatment, and advanced transportation projects, such as establishing a private airport in the governorate, and not to focus on repeatedly including service projects of a traditional nature in annual plans. Some governorates and ministries suffer from administrative and technical weakness. In the procedures for implementing some projects, as well as the administrative routine, bureaucracy, and centralization that characterize ministries and local government institutions in the governorates, not to mention quotas, the absence of proper planning, and the overlapping of powers, in addition to the widespread phenomenon of administrative and financial corruption, given the importance of infrastructure projects, the process of planning and implementing them, and the amount spent on them. Huge money and the impact of these projects on society, especially service ones, and the responsibility of the local administration towards them. It was necessary for the higher regulatory authorities to take their role in monitoring and auditing those projects that are implemented by these departments by examining the annual plans drawn up for infrastructure projects and their proportionality with reality. services, the mechanism for implementing them, and the amount of annual allocations allocated to them, which is therefore reflected in the possibility of evaluating the performance of those departments according to the results of auditing and measuring the effectiveness and efficiency of the local administration in achieving the goals contained in its strategic plan drawn up regarding infrastructure projects.